SAT0649 Changes in cartilage quality (DGEMRIC) following knee joint distraction or high tibial osteotomy: a two-year follow-up. (15th June 2017) - Besselink, N; Mastbergen, S; Vincken, K; Bartels, L; Concepcion, A; Marijnissen, AK; Lafeber, F
Abstract : Background: Since abnormal loading can cause onset and progression of OA, unloading the affected compartment of an osteoarthritic knee, should slow down OA progression, or even enable joint repair. High tibial osteotomy (HTO) is a well-known unloading approach for treating unilateral compartment osteoarthritis (OA) with mechanical axis deviation. Transient unloading using knee joint distraction (KJD) has demonstrated a progressive decrease in pain, normalization of function, and an increase in cartilage thickness 1 . Although both treatments show indications of joint repair, there is limited information about the actual quality of the regenerated tissue. Objectives: To evaluate the change in quality of the repaired cartilaginous tissue using dGEMRIC after KJD or HTO treatment. Methods: 40 patients (20 with KJD, and 20 with HTO), treated for medial tibiofemoral OA, are included in this study. Radiographic changes, clinical changes, and changes in cartilage quality are evaluated after one and two years follow-up. Joint space width (JSW) is evaluated on weight-bearing radiographs. Clinical improvement is evaluated by Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and Visual Analogue Scale (VAS) pain score. In order to evaluate the quality of the (newly formed) cartilaginous tissue, quantitative MRI analysis, in the form of Delayed gadolinium enhance Magnetic Resonance Imaging of cartilage (dGEMRIC) is performed. Results: A significantly increased medial (Δ1.15 mm, p<0.000), minimal (Δ0.93 mm, p<0.000) and mean (Δ0.79 mm, p=0.003) JSW one year after KJD, sustaining up until 2 years, was demonstrated (medial (Δ0.99 mm, p=0.002), minimal (Δ1.04 mm, p<0.000), mean JSW (Δ0.68 mm, p=0.027)). Similarly, medial (Δ0.49 mm, p=0.017) and minimal (Δ0.32 mm, p=0.023) JSW were significantly increased one year after HTO, sustaining up until 2 years (medial: Δ1.03 mm, p<0.000, minimal: Δ0.72 mm, p=0.015), after which mean JSW (Δ0.46 mm, p=0.030) is also significantly increased. Both interventions led to clinical improvement, observed as an increase in WOMAC after one year (KJD: Δ36.89, p<0.000, HTO: Δ33.74, p<0.000) and two years (KJD: Δ32.52, p<0.000, HTO: Δ24.19, p=0.002), and a decrease in VAS Pain, after one year (KJD: Δ-30.79, p=0.001, HTO: Δ-41.89, p<0.000) and two years (KJD: Δ-30.50, p=0.004, HTO: Δ-34.64, p<0.000). However, no statistically significant changes in cartilage quality were found after KJD or HTO, not in the medial and lateral compartments of the tibiofemoral joint, nor in the separate ROIs (see figure 1 ). Conclusions: Treatment of medial compartmental OA by either HTO or KJD leads to alleviation of pain and recovery of function, achieved one year after either intervention, and maintained for another year. Within the first year after treatment, KJD shows a statistically significantly higher increase in WOMAC as compared to HTO. Both treatments led to a statistically significant increase in JSW after one and two years, postponing the natural osteoarthritis progression rate. No statistically significant change in the quality of newly formed cartilaginous tissue could be detected by dGEMRIC. References: van der Woude et al. Knee joint distraction compared with high tibial osteotomy. 2016. Knee Surgery, Sports Traumatology, Arthroscopy, 1–11. Disclosure of Interest: None declared